Advances in Development of Novel Therapeutic Strategies against Multi-Drug Resistant Pseudomonas aeruginosa - Changhong Yin; Md Zahidul Alam; John T. Fallon; Weihua Huang (MDPI AG, 2024)
Pseudomonas aeruginosa (P. aeruginosa) with multi-drug resistance (MDR) is a major cause of serious healthcare-associated infections, leading to high morbidity and mortality. This opportunistic pathogen is responsible for various infectious diseases, such as those seen in cystic fibrosis, ventilator-associated pneumonia, urinary tract infection, otitis externa, and burn and wound injuries. Due to its relatively large genome, P. aeruginosa has great diversity and can use various molecular mechanisms for antimicrobial resistance. For example, outer membrane permeability can contribute to antimicrobial resistance and is determined by lipopolysaccharide (LPS) and porin proteins. Recent findings on the regulatory interaction between peptidoglycan and LPS synthesis provide additional clues against pathogenic P. aeruginosa. This review focuses on recent advances in antimicrobial agents and inhibitors targeting LPS and porin proteins. In addition, we explore current and emerging treatment strategies for MDR P. aeruginosa, including phages, vaccines, nanoparticles, and their combinatorial therapies. Novel strategies and their corresponding therapeutic agents are urgently needed for combating MDR pathogens.